Emotions and coping strategies of health care workers working in different hospitals of Chitwan during COVID-19 pandemic - Sharma, Kalpana; Joshi, Alisha; Poudyal, Sunita; Khatiwada, Kabita; Dhakal, Shankar; Neupane, Harish Chandra (Journal of Chitwan Medical College, 2020)
Background: Health Care Workers (HCWs) face huge emotional burden to balance the fundamental “duty to treat” with their parallel duties to family and loved ones. This study aimed to explore emotions and coping strategies of HCWs working in hospitals during COVID-19 Pandemic. Methods: This cross-sectional survey consisted 482 randomly selected HCWs working in five government and private hospitals of Chitwan. Data were collected using self-administered structured questionnaire for emotions and Brief COPE questionnaire for coping strategies. Forms were distributed to the HCWs using Google Form. Collected data were analysed using descriptive and inferential statistics. Results: Majorities of the HCWs were moderate to very much worried to do their job (75.3%), infecting family members/others (74.9%), lack of government steps for infection control (74.1%), getting infections from patients (67.9%), lack of treatment protocol (67.6%), inadequate specialty hospitals (64.7%) , man powers (61.4%), increasing COVID-19 cases (60.4%) as well as they avoided social gathering (72.8%). Nurses, female and HCWs with bachelors’ level experienced more emotional reactions (anxiety, sadness, shock, anger and enthusiasm) compared to doctors, male and HCWs with master and above education (p=<0.05). Adoption of coping strategies was higher among nurses compared to doctors (p=<0.05). Shock and sadness were the significant predictors of problem focused coping whereas anxiety and anger were the significant predictors of emotion-focused coping. Conclusions: Negative emotions and adoption of coping strategies are common among HCWs during this pandemic. Therefore, government and concern authorities need to organize screening program and psychological interventions for HCWs using identified predictors to enhance their mental wellbeing.